Genetic study of the hepcidin gene (HAMP) promoter and functional analysis of the c.-582A > G variant - Domínguez Fernando; Quinteiro Celsa; Campos Joaquín; González-Quintela Arturo; Parajes Silvia; Loidi Lourdes (BMC Genetics, 2010)
Abstract Background Hepcidin acts as the main regulator of iron homeostasis through regulation of intestinal absorption and macrophage release. Hepcidin deficiency causes iron overload whereas its overproduction is associated with anaemia of chronic diseases. The aims of the study were: to identify genetic variants in the hepcidin gene (HAMP) promoter, to asses the associations between the variants found and iron status parameters, and to functionally study the role on HAMP expression of the most frequent variant. Results The sequencing of HAMP promoter from 103 healthy individuals revealed two genetic variants: The c.-153C > T with a frequency of 0.014 for allele T, which is known to reduce hepcidin expression and the c.-582A > G with a 0.218 frequency for allele G. In an additional group of 224 individuals, the c.-582A > G variant genotype showed no association with serum iron, transferrin or ferritin levels. The c.-582G HAMP promoter variant decreased the transcriptional activity by 20% compared to c.-582A variant in cells from the human hepatoma cell line HepG2 when cotransfected with luciferase reporter constructs and plasmid expressing upstream stimulatory factor 1 (USF1) and by 12-14% when cotransfected with plasmid expressing upstream stimulatory factor 2 (USF2). Conclusions The c.-582A > G HAMP promoter variant is not associated with serum iron, transferrin or ferritin levels in the healthy population. The in vitro effect of the c.-582A > G variant resulted in a small reduction of the gene transactivation by allele G compared to allele A. Therefore the effect of the variant on the hepcidin levels in vivo would be likely negligible. Finally, the c.-153C > T variant showed a frequency high enough to be considered when a genetic analysis is done in iron overload patients.